2020
DOI: 10.3390/su12072849
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of 1.5 °C and 2 °C Global Warming on Net Primary Productivity and Carbon Balance in China’s Terrestrial Ecosystems

Abstract: Assessing potential impacts of 1.5 • C and 2 • C global warming and identifying the risks of further 0.5 • C warming are crucial for climate adaptation and disaster risk management. Four earth system models in the Coupled Model Intercomparison Project Phase 5 (CMIP5) and a process-based ecosystem model are used in this study to assess the impacts and potential risks of the two warming targets on the carbon cycle of China's terrestrial ecosystems. Results show that warming generally stimulates the increase of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Thus the increase in respiration caused by the warming in the long-term (around 4℃, Figure 11a) was projected to exceed the increase in photosynthesis, which was mani-fested as a significant negative correlation between temperature increase and NPP changes (Figure 11d). Similar to our results, Yu et al (2020) suggested that moderate warming (1.5℃) under the RCP4.5 scenario would be beneficial to the increase in NPP, but further warming (2℃) may lead to a decrease in NPP. Therefore it is necessary to prepare for the management and adaptation of the climate change risk faced by the ecosystem, though a moderate climate change may have a positive influence.…”
Section: Discussionsupporting
confidence: 90%
“…Thus the increase in respiration caused by the warming in the long-term (around 4℃, Figure 11a) was projected to exceed the increase in photosynthesis, which was mani-fested as a significant negative correlation between temperature increase and NPP changes (Figure 11d). Similar to our results, Yu et al (2020) suggested that moderate warming (1.5℃) under the RCP4.5 scenario would be beneficial to the increase in NPP, but further warming (2℃) may lead to a decrease in NPP. Therefore it is necessary to prepare for the management and adaptation of the climate change risk faced by the ecosystem, though a moderate climate change may have a positive influence.…”
Section: Discussionsupporting
confidence: 90%
“…Temperature is an important limiting factor of productivity dynamics in mid-latitude steppe ecosystems in the Northern Hemisphere [41,42]. Our study shows that there was a negative correlation between temperature and NPP in both grass-and shrub-dominated biomes during the growing season.…”
Section: Npp Dynamics and Main Driving Processesmentioning
confidence: 59%
“…The PLUS model is developed by Liang et al of China University of Geosciences (Wuhan) [30]. Studies have shown that the PLUS model has the ability to simulate the patchlevel evolution of land use landscapes [26,48,49]. In order to enhance the dependability of LULC simulation, the driving factors, LULC transfer rule, neighborhood weights, and space restriction, were set in the PLUS model.…”
Section: Lulc Spatial Simulation By Plusmentioning
confidence: 99%